1998
DOI: 10.1093/emboj/17.22.6689
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of the embryonic lethal hematopoietic defect reveals a critical role for GATA-2 in urogenital development

Abstract: Mutations resulting in embryonic or early postnatal lethality could mask the activities of any gene in unrelated and temporally distinct developmental pathways. Targeted inactivation of the transcription factor GATA-2 gene leads to mid-gestational death as a consequence of hematopoietic failure. We show here that a 250 kbp GATA-2 yeast artificial chromosome (YAC) is expressed strongly in both the primitive and definitive hematopoietic compartments, while two smaller YACs are not. This largest YAC also rescues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
130
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 52 publications
3
130
0
1
Order By: Relevance
“…However, there are at least an equal number of examples of tissues in which this transcription factor is robustly expressed but also for which its in vivo requirement has not yet been completely elucidated. Because it is well established that Gata2 null mutants expire from hematopoietic failure (2) and that Gata2 YAC-rescued null mutants, after surmounting the lethal hematopoietic block, expire from urogenital patterning failures (6), it seemed reasonable to ask: if both of these embryonic deficiencies were complemented by a transgene bearing activities that would correct both deficiencies, would the animals survive? The alternative, which might have been expected in this case, is that the animals would probably not survive to reproductive age, but expire of a second perinatal lethal urogenital failure (due to the anticipated absence from the transgene of any urogenital epithelia-complementing activity), or even from a deficiency in some new tissue that was regulated by an enhancer located outside the boundaries circumscribed by the linked BAC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there are at least an equal number of examples of tissues in which this transcription factor is robustly expressed but also for which its in vivo requirement has not yet been completely elucidated. Because it is well established that Gata2 null mutants expire from hematopoietic failure (2) and that Gata2 YAC-rescued null mutants, after surmounting the lethal hematopoietic block, expire from urogenital patterning failures (6), it seemed reasonable to ask: if both of these embryonic deficiencies were complemented by a transgene bearing activities that would correct both deficiencies, would the animals survive? The alternative, which might have been expected in this case, is that the animals would probably not survive to reproductive age, but expire of a second perinatal lethal urogenital failure (due to the anticipated absence from the transgene of any urogenital epithelia-complementing activity), or even from a deficiency in some new tissue that was regulated by an enhancer located outside the boundaries circumscribed by the linked BAC.…”
Section: Discussionmentioning
confidence: 99%
“…We showed several years ago that Gata2 null mutant embryonic lethality could be rescued by complementation with a 247-kbp transgenic yeast artificial chromosome (YAC) 3 bearing sequences from Ϫ174 to ϩ73 kbp (revised endpoints relative to the Gata2 translational initiation site); the YAC contains all of the regulatory information required to rescue Gata2 function in primitive and definitive hematopoiesis (6). We subsequently found that Gata2 hematopoietic regulatory activity is conferred by at least two distinct cooperative cis elements, one lying about 170 kbp 5Ј to the gene and another lying somewhere between 40 and 100 kbp 5Ј.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…And the interaction between GATA-2 and Pit-1 can lead to genespecific action and differentiation of TSH-secreting adenomas. Thus, GATA-2, which earlier in development is required for the expansion of hematopoietic precursors (33) and the development of the placental trophoblast (34) and urogenital system (35), also plays a critical role in pituitary cell type determination (15).…”
Section: Discussionmentioning
confidence: 99%